Functional Outcome Scores With Standard Myoelectric Prostheses in Below-Elbow Amputees. (February 2019) - Salminger, Stefan; Vujaklija, Ivan; Sturma, Agnes; Hasenoehrl, Timothy; Roche, Aidan D.; Mayer, Johannes A.; Hruby, Laura A.; Aszmann, Oskar C.
Abstract : Objective: The aim of the study was to report normative outcome data of prosthetic hand function in below-elbow amputees using four different objective measurements closely related to activities of daily living. Design: Seventeen patients who underwent prosthetic fitting after unilateral below-elbow amputation were enrolled in this study. Global upper extremity function was evaluated using the Action Research Arm Test, Southampton Hand Assessment Procedure, the Clothespin-Relocation Test, and the Box and Block Test, which monitor hand and extremity function. Results: The patients achieved a mean ± SD Action Research Arm Test score of 35.06 ± 4.42 of 57. The mean ± SD Southampton Hand Assessment Procedure score was 65.12 ± 13.95 points. The mean ± SD time for the Clothespin-Relocation Test was 22.57 ± 7.50 secs, and the mean ± SD score in the Box and Block Test was 20.90 ± 5.74. Conclusions: In the current economic situation of health care systems, demonstrating the effectiveness and necessity of rehabilitation interventions is of major importance. This study reports outcome data of below-elbow amputees and provides a useful guide for expected prosthetic user performance.